Operations management : sustainability and supply chain management / Jay Heizer; Barry Render; Chuck Munson - Heizer, Jay
"Operations Management: Sustainability and Supply Chain Management presents a broad introduction to the field of operations in a realistic and practical manner, while offering the largest and most diverse collection of issues on the market. Solved problems and worked examples found in the 13th Edition provide ample support -- to help readers better understand concepts important to today's operations management professionals."